VDC_100102371237.0X000001. Issue 10 (October 2018) - Malek, Kirollos S.; Namm, Jukes P.; Garberoglio, Carlos A.; Senthil, Maheswari; Solomon, Naveen; Reeves, Mark E.; Lum, Sharon S.
Balancing resident education with operating room (OR) efficiency, while accommodating different styles of surgical educators and learners, is a challenging task. We sought to evaluate variability in operative time for breast surgery cases. Accreditation Council for Graduate Medical Education case logs of breast operations from 2011 to 2017 for current surgical residents at Loma Linda University were correlated with patient records. The main outcome measure was operative time. Breast cases were assessed as these operations are performed during all postgraduate years (PGY). Breast procedures were grouped according to similarity. Variables analyzed included attending surgeon, PGY level, procedure type, month of operation, and American Society of Anesthesiologists class. Of 606 breast cases reviewed, median overall operative time was 150 minutes (interquartile range 187–927). One-way analysis of covariance demonstrated statistically significant variation in operative time by attending surgeon controlling for covariates (PGY level, procedure, American Society of Anesthesiologists class, and month) ( P = 0.04). With institutional OR costs of 30 per minute, the average difference between slowest and fastest surgeon was 2400 per case [(218–138) minutes 3 30/min]. Minimizing variability for common procedures performed by surgical educators may enhance OR efficiency. However, the impact of case length on surgical resident training requires careful consideration.